The perspectives of EFL learners on the video use in language classrooms - OĞUL, VERDA GİZEM; TOMAK, BURAK (My University, 2012)
With the improvement in technology in recent years, language teaching methodology has changed to a certain extent. Thus, teachers have started to make their lessons more efficient with the integration of the recent technology in the lessons. To illustrate, videos have started to be used in classes instead of audio players and tape recorders. The importance of video use in language classes has already been mentioned and it is a well-known fact in the field (Ur, 1984; Singer & Singer, 1983; Canning-Wilson,2000). However, nobody knows what will happen when the videos brought to the class have been created by thestudents themselves and their pedagogical implications. This study has been conducted whether the students have benefited from the videos that they have created due to the project assigned to them and a comparison between the videos brought by the teacher and the student videos has also been made on thebenefits of both. In order to figure out the educational benefits, students were given a project which required them to create a video in which they were playing by using the vocabulary and the structures they had learned so far. They were given a questionnaire before the videos were shown. Then, both the student videos and videos brought by the teacher were shown. Another questionnaire was given just after these presentations. It has been found out that students prefer videos brought by the teacher rather than the ones created by themselves because of several reasons. They have also preferred to have videos related to the target culture. Furthermore, there are some practical implications of the video use for education as well.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Video use; Students’ videos; Videos brought by the teacher